Jiwa Keberagamaan Generasi Milenial di Kelurahan Titi Kuning Kecamatan Medan Johor - Rahimah Kumullah; Husnel Anwar (UIN Sumatera Utara, 2023)
Generation is marked by the increasing use of digital media and technology. With the progress of the development of the global world has caused a change in perspective. The level of perspective of the millennial generation is more progressive about religion. This is developing in line with advances in technology for easy access to information. The results of the study show 1) The diversity of adolescents is seen from five elements. a) The subject's faith admits that he believes in the existence of Allah, Allah as his Lord and protector. God who gives health and sustenance. b) Knowledge and understanding of religious teachings, the subject knows about Islam from the pillars of Islam. c) Ritual worship, all subjects have performed ritual worship, namely prayer, fasting, zakat. d) The subject's religious experience has felt his religious experience such as feeling very happy to pray, pray midnight, dhuha and make fortune always smooth. e) Consequences of faith, subjects have solidarity among friends in the form of helping each other, being polite to older people, working together, and helping each other among friends is a form of worship that they consider important in life. 2) The origin of diversity in the millennial generation, the subject gains knowledge of the basics of different religions. Most get religious knowledge from their parents, and get religious education from certain institutions. In the millennial era, it is not only family, educational institutions, friendship circles, and organizations that are factors that influence the process of religious learning for young Muslims. Social media actually contributes to student religious learning as a Go-Jek partner. Because of current technological developments, those who used to take part in studies by coming to mosques in this millennial era, students only watch studies via the internet or YouTube channel. After conducting research, this research focuses on the religious spirit and religious origins of adolescents in the Titi Kuning Village, Medan, Johor. This study uses the theory of Starkan an Glock, namely diversity with five dimensions: ideological, ritualistic, intellectual, experiential and consequential. This research method uses a type of qualitative research. Data Collection Techniques using Interview Methods or interviews, observation, and documentation. Miles and Huberman's qualitative data analysis technique.